Rancang Bangun Sistem Monitoring Kompresor Udara Di Area Utility Berbasis IOT - Supriyadi, Jajang; Abdul Rozak, Ojak (CV. Shofanah Media Berkah, 2025)
This research aims to design and develop an Internet of Things (IoT)-based monitoring system for air compressors in the utility area, in order to enhance efficiency and enable real-time monitoring. The system utilizes a Pressure Transmitter sensor ( 0 – 12 bar ) to measure air pressure and a PZEM-004T sensor to measure the voltage and current of the compressor. The collected data is transmitted via a microcontroller to the Blynk application and displayed on a web-based dashboard. The research employs a system design method, which includes planning, hardware and software implementation, and testing. System evaluation is conducted using span error calculations to ensure the accuracy of the displayed data. The results show that the system successfully monitors air pressure, voltage, and current in real time with an acceptable level of accuracy. The data can be accessed online through the dashboard, allowing users to remotely monitor the compressor's performance effectively.